Glosa do wyroku Sądu Najwyższego z dnia 23 lipca 2020 roku, III KK 281/19 : Usiłowanie nieudolne przestępstwa groomingu z art. 200a § 2 k.k. - Kwiecień, Konrad (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The commentary presents the issue of criminal liability of a person rasing mistake of age as a defense in criminal cases under Article 200a of the Criminal Code (grooming) based on ruling of the Supreme Court of July 23, 2020, III KK 281/19. Two positions, different both in doctrine and jurisprudence, have been outlined regarding the nature of the type of criminal act described in Article 200a, particularly with regard to the possibility of applying regulations on inchoate offences. The purpose of this commentary is to argue why the interpretive direction adopted by the Supreme Court in this ruling is correct and mostly in line with the current state of the law.
Keywords: grooming; inefficient attempt; pedophile hunters; civic provocation